(untitled) (Africa Development, 2021)
Selected papers from the 12th CODESRIA General Assembly, except the ones written by Thandika Mkandawire and Tabona Shoko Contents Running While Others Walk: Knowledge and the Challenge of Africa’s Development Thandika Mkandawire ..................... 1 Gestion des espaces publics au Congo-Brazzaville : le cas des parkings Etanislas Ngodi .................................... 37 The National Project as a Public Administration Concept: The Problematic of State Building in the Search for New Development Paradigms in Africa Tukumbi Lumumba-Kasongo...................... 63 Médias et publicisation de la sphère privée au Cameroun Christian Bios Nelem ........................ 97 Commodifying the Female Body: Xenophobic Violence in South Africa Naomi Nkealah........................ 123 L’espace public au ras du sol en postcolonie : travail de l’imagination et interpellation du politique au Cameroun Claude Abé................................. 137 Higher Education as an African Public Sphere and the University as a Site of Resistance and Claim of Ownership for the National Project N’Dri T. Assié-Lumumba ................... 175 Le paradoxe de l’espace public dans la ville algérienne Djounid Hadjidj ....................... 207 (Re)Venturing into the Public Sphere: Historical Sociology of ‘August Meeting’ among Igbo Women in Nigeria Akachi Odoemene ............................ 219 Ethnicisation du domaine public et construction de l’État : pistes pour transcender une antinomie Emmanuel Yenshu Vubo ................. 249 Shona Traditional Religion and Medical Practices: Methodological Approaches to Religious Phenomena Tabona Shoko ..................... 277